Accuracy of a Fixed Value Nasion Relator in Facebow Design - Charles W. Wilcox, DDS, MS1, James L. Sheets, DDS1 & Terry M. Wilwerding, DDS, MS2 (Journal of Prosthodontics)
This study examined whether a fixed value nasion relator accurately locates the orbitale in a patient population